Buckling resistance of axially loaded cold-formed steel columns. (September 2016) - Craveiro, Hélder D.; Paulo, João; Rodrigues, C.; Laím, Luís
Abstract: This paper reports an experimental campaign on the buckling behaviour of compressed single and built-up cold-formed steel columns. Four types of cross-sections were tested, namely, one single, one open built-up and two closed built-up, considering two end-support conditions, pin-ended and fix-ended. The obtained results were compared with the design predictions of EN1993-1-3:2004 and AISI S100-07. For pin-ended lipped channel columns the design predictions are in good agreement with the experimental results, however for the fix-ended columns the predictions may be conservative. For built-up columns was found that increasing the number of profiles may lead to unsafe design predictions. Highlights: Experimental research on the buckling resistance of cold-formed steel columns. Results were compared against the design predictions of EN1993-1-3:2004. For pin-ended lipped channel columns the agreement is very good. For fix-ended columns the design predictions may be conservative. For built-up columns the design predictions are in some extent unsafe.